MANFAAT RASIO KEUANGAN DALAM MEMPREDIKSI KEPAILITAN BANK NASIONAL - SUMANTRI SUMANTRI; TEDDY JURNALI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2010)
The aim of this research is to prove that CAMEL (capital, assets quality, management, earnings and liquidity) has significant effect to the bankruptcy using 68 registered bank in Bank Indonesia Directory from 2000 until 2005. This study uses CAMEL ratio according to Bank Indonesia regulation. Logit regression is used to test the hypothesis. The result shows only fixed asset to equity ratio, elimination of productive assets to productive assets ratio, return on asset, net interest margin, loan to deposit ratio have significant effect to the bankruptcy.